Study of Fast Switching Processes in Cadmium Telluride Based Structures - Kirichenko, M. V.; Drozdov, A. N.; Shkoda, D. S.; Zaitsev, R. V.; Khrypunov, G. S.; Minakova, K. O.; Nikitin, V. O. (Сумський державний університет, 2022)
One of the main requirements for modern radio electronic equipment is the issue of electromagnetic (EM) stability, which means the ability to maintain operating parameters during and after the action of pulsed EM radiation of various origins. The problem of ensuring EM stability is due to the fact that under the influence of EM pulses, overvoltage pulses appeared in the circuits, which is particularly prone to the destruction of semiconductor devices due to both the properties of the p-n junction and the specific thermal conductivity of semiconductor materials. At the same time, the effects of resistive switching are actively used in modern electronics, in particular, the work of memristors is based on resistive switching in oxides of transition metals. This effect of resistive switching has long been observed in CdTe, both on thick (more than 100 μm) single-crystal layers and in thin polycrystalline films. The novelty of the proposed work consists in the fact that switching processes between low and high conductivity states in CdTe films depend on various factors, such as the film thickness, its initial structure, the power of the switching pulse, and the contact properties. Thin film CdTe based structures were prepared by using vacuum deposition methods. The study of fast switching processes in manufactured Mo – cadmium telluride – Mo structures was carried out by measuring and further analytical processing of their amplitude-time characteristics under the action of EM pulses of nanosecond duration. It was found that the prototypes with a metallization diameter of 0.5 mm and 6 mm, made using the planar technology, have similar parameters: the switching time is at the level of 1-2 ns, similar values of the cutoff voltage and the course of its dependence on the pulse amplitude. The geometry of the contact metallization does not affect the switching parameters of structures, and in the manufacture of protection elements against EM pulses on their basis, an industrial technology for the formation of metallization can be used without the need for its excessive miniaturization.

Однією з головних вимог до сучасного радіоелектронного обладнання є питання електромагнітної стійкості, що означає здатність підтримувати робочі параметри під час і після дії імпульсного електромагнітного випромінювання різного походження. Проблема забезпечення електромагнітної стійкості пов'язана з тим, що під впливом ЕМ-імпульсів у ланцюгах виникають імпульси перенапруги, що призводять до руйнування напівпровідникових приладів внаслідок як властивостей p-n переходу, так і питомої теплопровідності напівпровідникових матеріалів. У той же час ефекти резистивного перемикання активно використовуються в сучасній електроніці, зокрема, робота мемристорів заснована на резистивному перемиканні в оксидах перехідних металів. Цей ефект резистивного перемикання вже давно спостерігається в CdTe, як на товстих (понад 100 мкм) монокристалічних шарах, так і в тонких полікристалічних плівках. Новизна запропонованої роботи полягає в тому, що процеси перемикання між станами з низькою і високою провідністю в плівках CdTe залежать від різних факторів, таких як товщина плівки, її початкова структура, потужність імпульсу перемикання, властивості контакту. Тонкоплівкові структури на основі CdTe були виготовлені методами вакуумного осадження. Вивчення процесів швидкого перемикання в виготовлених структурах Mo – телурид кадмію – Mo проводилося шляхом вимірювання та подальшої аналітичної обробки їх амплітудно-часових характеристик під дією електромагнітних імпульсів наносекундної тривалості. Встановлено, що прототипи з діаметром металізації 0,5 мм і 6 мм, виготовлені за планарною технологією, мають подібні параметри: час перемикання на рівні 1-2 нс, близькі значення напруги відсікання та хід її залежності від амплітуди імпульсу. Геометрія контактної металізації не впливає на параметри перемикання конструкцій, а при виготовленні елементів захисту від електромагнітних імпульсів на їх основі можна використовувати промислову технологію формування металізації без необхідності її надмірної мініатюризації.
Дослідження процесів швидкого перемикання в структурах на основі телуриду кадмію
Keywords: planar technology; geometry; impulse; планарна технологія; геометрія; імпульс